Species diversity of Selaginella in Mount Lawu, Java, Indonesia - AHMAD DWI SETYAWAN; SUTARNO SUTARNO; SUGIYARTO SUGIYARTO (Society for Indonesian Biodiversity, 2013)
Setyawan AD, Sutarno, Sugiyarto. 2013. Species diversity of Selaginella in Mount Lawu, Java, Indonesia. Biodiversitas 14: 1-9. Selaginella is a genus of ferns allies that lives in moist areas and requires water for fertilization; therefore it is often found in highlands. The aim of this research was to know species diversity of Selaginella in Mount Lawu and the vicinity areas. The research was conducted between July 2007 and November 2012 on the western and southern slopes of Mount Lawu, Central- and East-Java, Indonesia, with altitudes between 1100 and 2100 m a.s.l. The research included three sites and the vicinity areas, i.e. (i) Protected forest of Cemorosewu, (ii) Grojogansewu Natural Recreation Park, and (iii) KGPAA Mangkunagoro I (Ngargoyoso) Grand Forest Park. The research found nine selaginellas species, namely: S. aristata, S. ciliaris, S. involvens, S. opaca, S. ornata, S. plana, S. remotifolia, S. singalanensis and S. zollingeriana.